Implementation of Student Teams Achievement Division (STAD) Type Cooperative Learning to Improve Futsal Shooting in Grade VIII Students at SMP Muhammadiyah 2 Boyolali Special Program - Aryanto, Sapril Wiji; Indarto, Pungki; Sistiasih, Vera Septi (UNIVERSITAS NEGERI MAKASSAR, 2025)
Shooting is one of the basic futsal techniques that is very important for a player to master. This study aims to analyze the application of Student Teams Achievement Division (STAD) type learning in improving futsal shooting skills in grade VIII students at SMP Muhammadiyah 2 Boyolali Special Program. This research is experimental in the form of class actions. The sample involved in this study was 30 students of Class VIII of the SMP Muhammadiyah 2 Boyolali Special Program. Data collection was used for a futsal shooting test, then analysed using a paired sample t-test. The results of this study showed that the results of statistical analysis with a paired sample t-test obtained a t-cal value of 14.936 and a significance of 0.000 (p < 0.05), which showed that there was a significant difference between the pre-test and post-test results. It can be concluded that the STAD learning model has been proven to be effective in improving the futsal shooting skills of grade VIII junior high school students.